The cold, cold ground [compact disc, unabridged] : a Detective Sean Duffy novel - McKinty, Adrian (McKinty, Adrian. Troubles trilogy., 2012)
Northern Ireland, spring 1981. Hunger strikes, riots, power cuts, a homophobic serial killer with a penchant for opera, and a young woman's suicide that may yet turn out to be murder: on the surface, the events are unconnected, but then things-and people-aren't always what they seem. Detective Sergeant Duffy is the man tasked with trying to get to the bottom of it all.